Dynamics of deterministically positioned single‐bond surface‐enhanced Raman scattering from DNA origami assembled in plasmonic nanogaps. (30th September 2020) - Chikkaraddy, Rohit; Turek, Vladimir A; Lin, Qianqi; Griffiths, Jack; de Nijs, Bart; Keyser, Ulrich F; Baumberg, Jeremy J
Abstract: We study the dynamics of single bonds through the surface‐enhanced Raman scattering (SERS) from single SERS‐marker molecules containing a distinctive single alkyl bond. Assembly of the nanogaps and positioning of single molecules inside the electromagnetic hotspot are precisely controlled using DNA origami constructs. The observed SERS intensities and their spectral wandering, together with electromagnetic simulations, all confirm the role of picocavities in this nanogap geometry in allowing observation of SERS signatures from individual vibrating bonds. The strong electromagnetic field around each picocavity and the transient binding of the SERS‐marker molecule reveal significant modifications to bond vibrations and selection rules over time. Abstract : We study the dynamics of single alkyne (C≡C) bond vibrations through the surface‐enhanced Raman scattering (SERS). The C≡C is precisely positioned into the plasmonic cavity using DNA origami constructs. The individual gold adatom pulled out of nanoparticle facets form picocavities in this nanogap geometry in allowing observation of SERS signatures from individual vibrating bonds.